Evolution of a research field—a micro (RNA) example - Casey, Máire-Caitlín; Kerin, Michael J.; Brown, James A.; Sweeney, Karl J. (PeerJ, 2015)
Background. Every new scientific field can be traced back to a single, seminal publication. Therefore, a bibliometric analysis can yield significant insights into the history and potential future of a research field. This year marks 21 years since that first ground-breaking microRNA (miRNA) publication. Here, we make the case that the miRNA field is mature, utilising bibliometrics. Methods. Utilising the Web of Science™ (WoS) database publication and citation information, we charted the history of miRNA-related publications, describing and dissecting contributions by publication type (plus category, pay-per-view or open access), journal (highlighting dominant journals), by country, citations and languages. Results. We found that the United States of America (USA) publishes the most miRNA papers, followed by China and Germany. Significantly, publications attributed to the USA also receive the most citations per publication, followed by a close grouping of England, Germany and France. We also describe the relevance and acceptance of the miRNA field to different research areas, through its uptake in areas from oncology to plant sciences. Exploring the recent momentous change in publishing, we find that although pay-per view articles vastly out-number open-access articles, the citation rate of pay-per-view articles is currently less than double that of open-access. Conclusions. We believe the trends described here represent the typical evolution of a research field. By analysing publications, citations and distribution patterns, key moments in the evolution of this research area are recognised, indicating the maturation of the miRNA field and providing guidance for future research endeavours.
Keywords: miRNA; microRNA; Lin-4; Bibliometric; Let-7